Enhancing Healthcare Quality through Connected Care Monitoring: A Survey on Nurses' Knowledge, Attitude, and Practice in Wards (International Journal of Nursing Education, 2025)
BackgroundEnhanced Connected Care (ECC) monitoring, which fuses medical devices with continuous monitoring of patient vitals captured by a nursing dashboard, offers a better way to address patient safety and improve clinical outcomes. Nurses are the key players involved in the implementation of ECC, while their KAP towards the technology in place decides the success and efficacy of this innovation. The purpose of this study is to determine the level of knowledge among nurses regarding ECC, perceptions regarding its benefits/challenges, and drivers/inhibitors of its implementation in a hospital environment.MethodsA two-month cross-sectional study was conducted at Apollo Hospital – Jubilee Hills. Nurses with a minimum of six months of practice experience were invited to complete a structured questionnaire via Survey Monkey. A total of 125 Nurses participated voluntarily in the survey. Descriptive statistics using SPSS and thematic analysis for qualitative answers were used. The significant variables were nurses’ knowledge of ECC, confidence level, time saving per shift and the perceived barriers for implementation of ECC.ResultsSixty-one percent of nurses expressed high confidence in ECC usage, with increased comfort in ECC evident among younger (18–34 years) than older nurses. Time saved was substantial, with 47.2% saving 5–10 min per shift. There was a strong correlation between levels of knowledge and confidence (p = 0.009). The main cited benefits were enhanced patient safety (24%) and increased early deterioration detection (22.4%), although alarm burden and technical integration challenges constrained uptake.ConclusionECC monitoring can improve our patients and workflow but to be successful we need better training, tailored mid-career nurse support, and the right systems in place to drive alarm fatigue down. The solution to these challenges will enable wider adoption and better clinical outcomes.